Bilateral differences in coordination variability among injured and uninjured runners: A prospective study - Desai, G. A.; Gruber, A. H. (Journal of Biomechanics, 2022)
This prospective cohort study aimed to identify bilateral differences in coordination variability (CAV) to determine if limb-specific CAV or CAV asymmetry is associated with running-related overuse injury (RRI) development in recreational runners. Lower limb kinematics were collected at enrollment. Runners were classified as injured (n = 14) or controls (n = 17) based on RRI incidence during a = 6-month follow-up. Pelvis-thigh, knee-shank, knee-ankle, and shank-ankle CAV was quantified bilaterally within thirds of stance using modified vector coding. Wilcoxon Signed-Rank tests compared CAV between limbs within each group, and Wilcoxon Rank-Sum tests compared CAV asymmetry between groups (a = 0.05). Injured runners displayed elevated injured versus uninjured limb CAV during initial-stance for all couplings (p < 0.010,d(effect size) = 0.51-1.31) except pelvis-thigh (p = 0.060,d = 0.36). During mid-stance, the injured limb exhibited restricted knee-ankle CAV (p < 0.010,d = 0.413) and elevated pelvis-thigh CAV (p < 0.010,d = 0.23). Controls also displayed bilateral differences specifically in pelvis-thigh CAV across stance, shank-ankle CAV during initial-stance, in all couplings during mid-stance, and shank-ankle CAV during late-stance (p < 0.010-0.025,d = 0.09-0.63). Comparing CAV asymmetry between groups revealed lower asymmetry among injured runners compared with controls for knee-ankle coupling in mid-stance and all couplings except pelvis-thigh during late-stance (p < 0.010,d = 0.85-1.87). Injured runners also displayed greater knee-shank CAV asymmetry in mid-stance versus controls (p < 0.010,d = 0.85). Logistic regression (a = 0.05) revealed that between-limb CAV asymmetry did not predict RRI (p = 0.161), however, the odds of RRI were > 20% in the limb with either elevated shank-ankle CAV in initial-stance (p = 0.020) or elevated knee-ankle CAV in mid-stance (p = 0.043) than the contralateral limb. Therefore, limb-specific CAV rather than degree of CAV asymmetry may influence risk of RRI.